Terraced landscapes: an increasingly prominent cultural landscape type - Drago Kladnik; Alexandra Kruse; Blaž Komac (Acta Geographica Slovenica, 2017)
Over the past decades, attractive terraced landscapes composed of cultivated terraces have been increasingly dealt with in studies in geography, landscape architecture, ethnology, rural sociology, agronomy, pedology, and other spatial disciplines. Around 2000, several important research projects were carried out. The Terraced Landscapes Alliance (ITLA) was established, and terraced landscapes have also obtained their place within the European Geosciences Union (EGU) and EUCALAND. During this period, research on terraced landscapes has also intensified in Slovenia. All five articles featured in this special thematic issue of Acta geographica Slovenica are also briefly presented.